Pendidikan Karakter Berbasis Kearifan Lokal Melalui Nangun Sat Kerthi Loka Bali - Ni Putu Candra Prastya Dewi (STAHN Mpu Kuturan Singaraja, 2020)
Degradation of character appears to be the abandonment of local cultures by being replaced by foreign cultures which actually have a negative impact on the development of Indonesia's young generation, especially in Bali. Therefore it is necessary to have a character education based on local wisdom so that the younger generation does not forget the Balinese culture. The vision of the government that fosters local wisdom-based character is